TREND OF PUBLIC SERVICE APPLICATION ACCEPTANCE ANALYSIS: A SYSTEMATIC REVIEW USING THE PRISMA APPROACH - Amrulloh, Adikara Akbar; Akbar, Rasona Sunara; Fathya, Vita Nurul (Jurnal Administrasi Negara, 2025)
Indonesia's public service digital transformation has seen continuous development over the last five years, from 2020 to 2024. Digitalization is being applied across various sectors, including health, immigration, public service malls (MPP), local government, and the energy and financial sectors. This research aims to analyze the development of technology utilization in public services, identify the most frequently used analytical methods in studies related to public service applications over the past five years, and determine the factors influencing user satisfaction with public service applications. This study employs a Systematic Literature Review (SLR), guided by the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) approach. It gathered and analyzed various research works related to technology implementation in public services to identify development patterns, dominant analytical methods, and key factors in assessing user satisfaction with applications. The research findings indicate that the Technology Acceptance Model (TAM) has remained the most dominant method over the past five years (2020-2024). The most influential factors affecting user satisfaction with applications are system quality, information quality, perceived ease of use, and service quality. The main challenges in digital transformation implementation include lack of information dissemination, the digital divide, infrastructure limitations, and resistance to change. With the increasing adoption of technology, research on public services is now shifting from user acceptance analysis towards the evaluation of implementation success and the impact of digitalization policies.